The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/w9070506
|View full text |Cite
|
Sign up to set email alerts
|

NF-RO Membrane Performance for Treating the Effluent of an Organized Industrial Zone Wastewater Treatment Plant: Effect of Different UF Types

Abstract: Abstract:Reuse of water is necessary in Organized Industrial Zones (OIZ) due to excessive use of groundwater in semi-arid Turkey. Membrane treatment of the OIZ wastewater treatment plant (WWTP) effluents should be explored for new treatment options. In this study, three different UF membranes with variable molecular weight cutoff (MWCO) values (4, 10, and 250 kDa) were used to treat the effluent of an OIZ WWTP at laboratory scale. Six different nanofiltration (NF) and reverse osmosis (RO) membranes were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…The RMS roughness of the NF90 membrane was 61 nm, and that of BW30LE was 49.7 nm; the membrane with the rougher surface is more prone to fouling [ 24 ]. Similar results were obtained in previous studies—the NF90 membrane displayed severe fouling when used for wastewater treatment, which resulted in a lower level of water flux than RO [ 21 , 25 ]. A more detailed discussion is provided on membrane fouling to support the findings regarding water flux.…”
Section: Resultssupporting
confidence: 90%
“…The RMS roughness of the NF90 membrane was 61 nm, and that of BW30LE was 49.7 nm; the membrane with the rougher surface is more prone to fouling [ 24 ]. Similar results were obtained in previous studies—the NF90 membrane displayed severe fouling when used for wastewater treatment, which resulted in a lower level of water flux than RO [ 21 , 25 ]. A more detailed discussion is provided on membrane fouling to support the findings regarding water flux.…”
Section: Resultssupporting
confidence: 90%
“…The rejection mechanism of RO includes size exclusion, charge exclusion and physical-chemical interactions between solute and solvent [164,165]. As expected, RO retention capacities are better than NF due to its almost nonporous nature, reflected in higher removal of organic compounds, monovalent ions, TDS and conductivity [159,166,167]. As listed in Table 9, the conductivity removal by NF is usually effective, but not completely, ranging between 40% and 90%, while RO shows excellent separation performance on almost complete salinity removal.…”
Section: Nf/ro/fo-based Treatment Processes For Water Reusementioning
confidence: 71%
“…Pore blocking is found to be irreversible, while cake blocking is easily removed by simple backwashing, and irreversible blocking may be formed due to the organic macromolecules [22]. However, in another study, PVDF membranes showed a removable fouling character, with flux being nearly the same as before the operation [27]. Other studies of cake and pore blocking of the membranes also showed that pore blocking and cake formation are the dominant fouling mechanisms in PES membranes [28].…”
Section: Resistancesmentioning
confidence: 93%